Teacher peer excellence groups (TPEGs): Building communities of practice for instructional improvement. Issue 5 (7th August 2017) - Cravens, Xiu; Drake, Timothy A.; Goldring, Ellen; Schuermann, Patrick
Abstract : Purpose: The purpose of this paper is to study the viability of implementing a protocol-guided model designed to provide structure and focus for teacher collaboration from Shanghai in today's US public schools. The authors examine whether the new model, Teacher Peer Excellence Group (TPEG), fosters the desired key features of productive communities of practice where teachers can jointly construct, transform, preserve, and continuously deepen the meaning of effective teaching. The authors also explore the extent to which existing school conditions – principal instructional leadership, trust, teacher efficacy, and teachers' sense of school-wide professional community – enable or moderate the desired outcomes. Design/methodology/approach: Data for this paper are drawn from a series of surveys administered to teachers from 24 pilot schools in six school districts over two school years. Descriptive and multilevel modeling analyses are conducted. Findings: The findings provide encouraging evidence that, given sufficient support and guidance, teachers report higher levels of engagement in deprivatized practice and instructional collaboration. These findings also hold after controlling for key enabling conditions and school characteristics. Social implications: The TPEG approach challenges school leaders to take on the responsibilities of helping teachers make their practice public, sharable, and better – three critical objectives in the shift to develop the profession of teaching. Originality/value: The indication of TPEG model's positive impact on strengthening the features of communities of practice in selected public schools provides the impetus for further efforts in understanding the transformational changes needed and challenges ahead at the classroom, school, and district levels.